Design of a high power ultra wideband system using a fast impulse current generator (2011)
This thesis presents a DC-Charged high amplitude electromagnetic radiator. The radiator consists of a Half Impulse Radiating Antenna (HIRA) fed by a coaxial Pulse Forming Line (PFL), which is charged using a mechanism based on corona currents on floating electrodes. The theoretical background, the design process, the construction and the experimental characterization of the radiated signals are presented and discussed. A circuit model of the corona charging mechanism is proposed and validated.